Sosialisasi Inovasi material Menggunakan Silica Fume dan Fly Ash sebagai Bahan Tambah pada beton - Anastasia Septya Wardaningrum; Era Agita Kabdiyono; Ahmad Fachri Ilham Al Akmal; Iqbal Rusdiani; Kukuh Faizal Akhmad; Muhammad Khoirul Dzakwan (Asosiasi Dosen Muda Indonesia, 2026)
This title describes an activity (such as a seminar, workshop, or presentation) aimed at disseminating information (socialization) about an innovation in the field of construction materials. Many small-scale construction practitioners, craftsmen, or the general public still use conventional concrete mixing methods (only cement, sand, gravel, water). They do not understand that the addition of additives can significantly change the properties of concrete. Fly Ash (fly ash from coal combustion) and Silica Fume (residual silicon metal production) are industrial wastes that are abundantly produced. If not utilized, these materials often become environmental pollutants. In the field, this waste is often considered useless, even though it has high pozzolanic properties. Conventional concrete often has quite large micropores, making it susceptible to water seepage and cracking over time. Without additives, it is difficult to achieve high-quality concrete or watertight concrete at the greatest cost efficiency. In the field, cement use is often wasteful. Replacing some cement with Fly Ash or Silica Fume is a global solution that has not been widely implemented at the local/community level. The main objective of this activity is to bridge modern concrete technology with its applications in society to create better and more sustainable construction. The main focus of innovation is the use of two specific materials: Silica Fume and Fly Ash. These two materials—often byproducts or waste from other industries—are presented as additives mixed into concrete.